2017
DOI: 10.1128/aac.02515-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Type II Fatty Acid Synthesis Bypass in Staphylococcus aureus

Abstract: The need for new antimicrobials to treat bacterial infections has led to the use of type II fatty acid synthesis (FASII) enzymes as front-line targets. However, recent studies suggest that FASII inhibitors may not work against the opportunist pathogen Staphylococcus aureus, as environmental fatty acids favor emergence of multi-anti-FASII resistance. As fatty acids are abundant in the host and one FASII inhibitor, triclosan, is widespread, we investigated whether fatty acid pools impact resistance in clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…Recently, Gloux et al [90] addressed this question by collecting S. aureus samples for clinical and veterinary settings and plating them on selective media containing exogenous fatty acids and/or triclosan. They report 12% of 695 the isolates had modification in FASII genes.…”
Section: Evolutionary Changes In Bacterial Phospholipid Synthesis mentioning
confidence: 99%
“…Recently, Gloux et al [90] addressed this question by collecting S. aureus samples for clinical and veterinary settings and plating them on selective media containing exogenous fatty acids and/or triclosan. They report 12% of 695 the isolates had modification in FASII genes.…”
Section: Evolutionary Changes In Bacterial Phospholipid Synthesis mentioning
confidence: 99%
“…Furthermore, when cultured in the presence of porcine liver extracts S. aureus bacteria with non-synonymous mutations in the malonyl CoA-acyl carrier protein transacylase ( fabD) gene bypass the FASII pathway and incorporate long-chain polyunsaturated fatty acids such as C20:4 into their membranes [36]. Examination of a large panel of clinical isolates has indicated that it could be a common strategy of S. aureus to incorporate exogenous FA, overcoming its reliance on endogenous FA biosynthesis, and thus rendering ineffective FASII inhibitors such as the widely used biocide triclosan [37].…”
Section: Resultsmentioning
confidence: 99%
“…Adaptation to FASII inhibitors is not due to FASII mutations. Mutations in FASII initiation genes may 91 lead to antibiotic resistance (14,(17)(18)(19). We monitored mutations in FASII antibiotic-adapted USA300 92 or Newman strains by DNAseq, using FASII inhibitors triclosan or AFN-1252 (Table S1).…”
Section: Aureus 89 90mentioning
confidence: 99%
“…Anti-FASII 25 resistance due to mutations affecting the target enzyme or to horizontal transfer of an antibiotic-26 resistant gene homologue may occur and are often antibiotic-specific (15,16). In contrast, resistant 27 mutants that allow compensatory fatty acid utilization at both phospholipid positions were isolated 28 and also found in clinical isolates; these mutants map in FASII initiation genes distinct from the gene 29 encoding the antibiotic target protein (17)(18)(19). Despite emergence of mutations, continued FASII-30 targeted drug development is rationalized by the accepted postulate that the general wild type S. 31 aureus population must synthesize branched chain fatty acid anteiso 15:0 (ai15) to complete 32 membrane phospholipids (1, 3, 5, 8-11, 14, 20).…”
Section: Introduction 19 20mentioning
confidence: 99%
See 1 more Smart Citation